Screening for caregiver psychosocial risk in children with medical complexity: a cross-sectional study. Issue 1 (27th July 2020) - Verma, Rahul; Mehdian, Yasna; Sheth, Neel; Netten, Kathy; Vinette, Jean; Edwards, Ashley; Polyviou, Joanna; Orkin, Julia; Amin, Reshma
Abstract : Objective: To quantify psychosocial risk in family caregivers of children with medical complexity using the Psychosocial Assessment Tool (PAT) and to investigate potential contributing sociodemographic factors. Design: Cross-sectional study. Setting: Family caregivers completed questionnaires during long-term ventilation and complex care clinic visits at The Hospital for Sick Children, Toronto, Ontario, Canada. Patients: A total of 136 family caregivers of children with medical complexity completed the PAT questionnaires from 30 June 2017 through 23 August 2017. Main outcome measures: Mean PAT scores in family caregivers of children with medical complexity. Caregivers were stratified as 'Universal' low risk, 'Targeted' intermediate risk or 'Clinical' high risk. The effect of sociodemographic variables on overall PAT scores was also examined using multiple linear regression analysis. Comparisons with previous paediatric studies were made using T-test statistics. Results: 136 (103 females (76%)) family caregivers completed the study. Mean PAT score was 1.17 (SD=0.74), indicative of 'Targeted' intermediate risk. Sixty-one (45%) caregivers were classified as Universal risk, 60 (44%) as Targeted risk and 15 (11%) as Clinical risk. Multiple linear regression analysis revealed an overall significant model (p=0.04); however, no particular sociodemographic factor was a significant predictor of total PAT scores. Conclusion: Family caregivers of children with medical complexity report PAT scores among the highest of all previously studied paediatric populations. These caregivers experience significant psychosocial risk, demonstrated by larger proportions of caregivers in the highest-risk Clinical category.